RETRACTED: Revealing the Impacts of Banking Sector Development on Renewable Energy Consumption, Green Growth, and Environmental Quality in China: Does Financial Inclusion Matter? - Khan, Muhammad Asghar; Rehan, Raja (Frontiers in Energy Research, 2022)
China aims to reduce its carbon dioxide emissions and promote green growth. This study aims to examine the effect of banking sector performance indicators (banks assets and return on asset) and financial inclusion on renewable energy consumption, green growth, and carbon emissions for China from 1995 to 2020 using the ARDL approach. The long-run results suggest that bank assets increase renewable energy consumption and green growth. While return on assets also increases green growth and decreases carbon emission in the long run. Financial inclusion enhances renewable energy consumption and green growth, curbing CO2 emissions. Banking sector performance and financial inclusion have short-run effects on renewable energy consumption, green growth, and carbon dixoside emissions. The findings thus point to the need for policies that promote banking sector performance and financial inclusion to boost green growth and alleviate CO2 emissions.